2018
DOI: 10.1016/j.jaad.2018.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and cytokine levels induced by intralesional photodynamic therapy and 630-nm laser in a case series of basal cell carcinoma

Abstract: Armstrong AW. Who do you prefer? A study of public preferences for health care provider type in performing cutaneous surgery and cosmetic procedures in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Thissen et al 17 demonstrated that an intracutaneous administration of ALA of concentration as low as 2% resulted in increased fluorescence levels and higher protoporphyrin IX concentrations compared to topical administration of 20% ALA. Cappugi et al reported the efficacy of this form of treatment in nodular BCC, and it has been described in the treatment of superficial BCC, squamous cell carcinoma and the treatment of parasitic diseases. [18][19][20][21] Suárez-Valladares et al 22 reported that in all BCC cases who underwent intralesional PDT, the levels of IL-1β, IL-8 and IL-6 increased after treatment indicating a distinct pattern of inflammatory response. The main limitation of our study was the small sample size of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thissen et al 17 demonstrated that an intracutaneous administration of ALA of concentration as low as 2% resulted in increased fluorescence levels and higher protoporphyrin IX concentrations compared to topical administration of 20% ALA. Cappugi et al reported the efficacy of this form of treatment in nodular BCC, and it has been described in the treatment of superficial BCC, squamous cell carcinoma and the treatment of parasitic diseases. [18][19][20][21] Suárez-Valladares et al 22 reported that in all BCC cases who underwent intralesional PDT, the levels of IL-1β, IL-8 and IL-6 increased after treatment indicating a distinct pattern of inflammatory response. The main limitation of our study was the small sample size of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Once the inflammatory process is triggered in vitro, inflammatory mediators initiate the production of cytokines, which play key roles in the inflammatory response [51]. Previous studies have analyzed the action of PDT as a therapeutic method through the production of cytokines, observing an increase in pro-inflammatory cytokines (IL-1β, IL-8, IL-6 and MCP1), highlighting that the action of PDT has three phases: generation of ROS; expression of local endothelial damage and the mechanisms of the disease, so patients who responded to PDT had their levels of proinflammatory cytokines increased, as a response to the inflammatory process [52][53][54]. Also, in comparison with PDT and LED therapy, PDT proved to be more effective in reducing cytokine expression 24 hours after irradiation, when compared to the action of LED alone (therapeutic LED effect) [55,56].…”
Section: B Amentioning
confidence: 99%